IL10- and IL35-Secreting MutuDC Lines Act in Cooperation to Inhibit Memory T Cell Activation Through LAG-3 Expression - Koga, Marianna M.; Engel, Adrien; Pigni, Matteo; Lavanchy, Christine; Stevanin, Mathias; Laversenne, Vanessa; Schneider, Bernard L.; Acha-Orbea, Hans (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are professional antigen-presenting cells involved in the initiation of immune responses. We generated a tolerogenic DC (tolDC) line that constitutively secretes interleukin-10 (IL10-DCs), expressed lower levels of co-stimulatory and MHCII molecules upon stimulation, and induced antigen-specific proliferation of T cells. Vaccination with IL10-DCs combined with another tolDC line that secretes IL-35, reduced antigen-specific local inflammation in a delayed-type hypersensitivity assay independently on regulatory T cell differentiation. In an autoimmune model of rheumatoid arthritis, vaccination with the combined tolDCs after the onset of the disease impaired disease development and promoted recovery of mice. After stable memory was established, the tolDCs promoted CD4 downregulation and induced lymphocyte activation gene 3 (LAG-3) expression in reactivated memory T cells, reducing T cell activation. Taken together, our findings indicate the benefits of combining anti-inflammatory cytokines in an antigen-specific context to treat excessive inflammation when memory is already established.